2018
DOI: 10.14814/phy2.13910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle cooling on kinetics of pulmonary oxygen uptake and muscle deoxygenation at the onset of exercise

Abstract: This study investigated effects of skeletal muscle cooling on the metabolic response and kinetics of pulmonary oxygen uptake (trueV˙O2) and skeletal muscle deoxygenation during submaximal exercise. In the cooling condition (C), after immersion of the lower body into 12°C water for 30 min, eight healthy males performed 30‐min cycling exercise at the lactate threshold while undergoing thigh cooling by a water‐circulating pad. In the normal condition (N) as control, they conducted the same exercise protocol witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Vastus lateralis muscle and skin temperatures were measured continuously (at a distance of 50% between the greater trochanter and lateral condyle of the femur) before (after entering the chamber) and during exercise and at 3 h post-exercise. Muscle temperature was evaluated non-invasively (every 2 s) using a probe-type thermometer (Core temp CM-210; TERMO Co., Ltd., Tokyo, Japan) ( Wakabayashi et al, 2018 ). Skin temperature was monitored (every 1 s) using a probe-type thermometer and logger (NT Logger N543; Nikkiso-Therm Co., Ltd., Tokyo, Japan) ( Maruyama et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Vastus lateralis muscle and skin temperatures were measured continuously (at a distance of 50% between the greater trochanter and lateral condyle of the femur) before (after entering the chamber) and during exercise and at 3 h post-exercise. Muscle temperature was evaluated non-invasively (every 2 s) using a probe-type thermometer (Core temp CM-210; TERMO Co., Ltd., Tokyo, Japan) ( Wakabayashi et al, 2018 ). Skin temperature was monitored (every 1 s) using a probe-type thermometer and logger (NT Logger N543; Nikkiso-Therm Co., Ltd., Tokyo, Japan) ( Maruyama et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This monitor measures skin surface temperature beneath a thermal insulating pad containing a heater, which equilibrates the skin temperature with the deep tissue temperature when heat flow from the skin is maintained at zero. The consistency between muscle temperature measured using a needle thermocouple and the zero heat flow method was evaluated previously (Togawa et al, 1976; Wakabayashi et al, 2018). Tre, skin, and deep thigh temperature, HR were measured every 3 min during the experiment.…”
Section: Measurementsmentioning
confidence: 99%
“…Study has demonstrated that the tissue saturation index (TSI) in muscle tissue gradually decreases with increasing exercise intensity 27 . Decreased TSI in muscle tissue leads to an increase in blood lactate concentration 26,28 . Lactate is an intermediate of glucose metabolism and its increase may be related to conscious fatigue 29,30 .…”
mentioning
confidence: 99%